Identification of Palm Oil Mill Throughput Capacity of 60 tons/hour (Case Study at XYZ Palm Oil Mill) - Istianto Budhi Rahardja; Sulistiono Sulistiono; Anwar Ilmar Ramadhan (Journal of Applied Sciences and Advanced Technology, 2020)
Throughput is the ability of a company's production unit to process raw materials into final products that have value, in accordance with established standards. Palm Oil Mill (PKS) is a processing company for raw materials in the harvest of palm oil in the form of Fresh Fruit Bunches processed into Crude Palm Oil (CPO) and Palm Kernel Oil (PKO) products and their by-products in the form of solid waste (empty bunches, fiber, shells) and liquid. PKS production can be achieved throughput produced by looking at the production process that occurs in each work unit, namely: the value of the capacity of the stew is done, sequencing time, steam boiler requirements, Material Balance. The capacity owned by PKS XYZ is 60 tons/hour, does not meet the targeted throughput, where the sterilizer capacity is only able to reach 45 tons/hour, sequencing time is 45 minutes, the steam boiler produced is not sufficient to produce 60 tons of PKS/hour, and the existing Material Balance is not met, which are 38 tons/hour.